Profit efficiency and its determinants in the agricultural sector: A Bayesian approach - Marta Arbelo-Pérez; Pilar Pérez-Gómez; Antonio Arbelo (Agricultural Economics (AGRICECON), 2023)
Most empirical studies evaluating efficiency in the agricultural sector estimate cost efficiency, assuming homogeneity across firms. However, achieving the goal of profit maximisation requires both minimising costs and maximising revenue. Unlike cost efficiency, the concept of profit efficiency considers the errors on both the input side and the output side, and thus, it is more appropriate for evaluating the overall performance of firms. This paper estimates profit efficiency and its determinants in the agricultural sector in Spain using a Bayesian stochastic frontier model with random coefficients. This methodology adequately captures the heterogeneity across firms in the industry. The results reveal, firstly, that agricultural firms in Spain are operating with an average profit inefficiency of 35.78% and, secondly, that this inefficiency is affected, albeit unevenly, by the size and age of the farm. Finally, the implications of these results for managers and public policies are discussed.